Evidence based study on the effect of Taijiquan intervention on autonomic nervous system in the elderly - Wu, Zhigui; Fang, Yurui; Li, Ju; Sun, Rongkun; Hou, Lijuan (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: Autonomic nervous system includes sympathetic and parasympathetic nerves. It is the central and peripheral nerve components that dominate and regulate the visceral function of the body. It plays an important role in controlling the physiological function: It controls and regulates the activities and secretion of various organs, blood vessels, smooth muscle and glands, and participates in endocrine regulation of glucose, fat, water and electrolyte metabolism, as well as body temperature, sleep and blood pressure. Under the control of cerebral cortex and hypothalamus, sympathetic parasympathetic system can both antagonize and coordinate the physiological activities of organs. At present, research shows that the functional health status of the elderly will gradually decline with age, the function and activity of nervous system decline, cognitive decline, even emotional disorders and other mental diseases. mainly manifested in the decrease of cardiac autonomic nervous system activity, the decrease of time-domain and frequency-domain indexes of heart rate, and the imbalance of blood pressure, pulse, respiration and endocrine. The main mechanism may be the dysfunction of cardiac sympathetic nerve and cardiac vagus nerve. Previous studies have confirmed that Taijiquan, as a low-intensity aerobic exercise, can improve the function of the main nervous system and the regulation ability of sympathetic parasympathetic nerve activity in the elderly; Long term Tai Chi exercise in various forms can effectively control blood pressure, improve local blood flow, balance the impulse of cardiac sympathetic nerve and cardiac vagus nerve, and promote the autonomous regulation of cardiovascular nerve. Renew and repair aging nerve cells; Stimulate metabolism; Enhance cardiovascular health; Improve the activity of autonomic nerve and restore the complex dynamic balance of mutual inhibition and restriction between the unbalanced sympathetic nerve and parasympathetic nervous system; Improve heart rate variability in the elderly; Maintain the state of autonomic nerve rejuvenation in the elderly. Due to the complex functional structure of autonomic nervous system, there are different research methods for its functional evaluation. Heart rate variability (HRV) contains important information about cardiovascular regulation, and its correlation index is recognized as a quantitative index to determine autonomic nerve activity. Analyzing heart rate variability index can indirectly quantitatively evaluate sympathetic and parasympathetic tension and balance. It can completely reflect the changes of body quiet state, exercise state and cardiac cycle after exercise. Therefore, this study evaluates the main indexes of human heart rate variability before and after Taijiquan intervention: standard deviation of normal RR intervals (SDNN), root-mean-square of difference-value of adjacent RR interval (RMSSD), low-frequency power (LF), high-frequency power (HF), low-frequency power/ high-frequency power (LF/HF) and so on. To analyze the activity of the nervous system. The activity of autonomic nerve was reflected through the comparison and analysis of various indexes. This paper will review and analyze the effects of Taijiquan on the autonomic nervous system of the elderly by meta-analysis. Methods: Through the retrieval of electronic literature databases (China journal full text database (CNKI), VIP database, Wan fang database, PubMed and web of Science), the retrieved literature types include journal papers and degree papers. The retrieval methods adopted include advanced retrieval and free combination retrieval. Inclusion criteria: (1) randomized controlled trial (RCT). (2) Subjects: healthy elderly people (3) Intervention measures: Taiji exercise intervention, the study must involve a clear motion cycle and single motion time. (4) OUTCOME MEASURES: The main outcome measures were time domain (SDNN, RMSSD) and frequency domain (LF, HF and LF/HF). A total of 73 evidence-based literatures on the impact of Taijiquan intervention on the autonomic nervous system of the elderly were collected to analysis. Cochrane16 evaluation system was used to evaluate the researchers independently evaluated the quality and offset risk of all the included literatures and extracted relevant data which were extracted from the selected literature, including the basic contents of the included literature (author, year of publication), the basic situation of the research objects (number of experimental group and control group, country), research design, total number of experimental population and total number of control population. The literatures were screened in turn according to the screening literature flow chart. Statistical software stata16 was used to conduct meta-analysis and evidence-based research on 11 literatures. The utility quantity and overall utility of each literature and expected indicators were calculated, and the exercise intervention efficacy was counted and the accuracy of effect value was estimated. Results: The literature was screened by literature filtering (Jadad scale). Finally, 11 articles were included in the meta-analysis, including 9 medium-quality research literatures with statistical significance. Statistical software stata16 was used to conduct meta-analysis and evidence-based research on 11 literatures. (1) Influence of Taijiquan Exercise on HRV time domain index: the research of SDNN and RMSSD included 6 groups, a total of 332 subjects (172 in Taijiquan exercise group and 172 in control group). Compared with the subjects included in the study, the heterogeneity test I2=94%, which showed that there was no heterogeneity between the studies. Therefore, there was a significant difference between the Tai Chi group and the control group by meta-analysis, SMD=0. 444, 94. 9% CI, P=0. 001. It shows that Taijiquan can effectively improve the SDNN and RMSSD levels of the elderly; (2) Influence of Taijiquan Exercise on HRV frequency domain indicators: frequency domain indicators include LF, HF and LF/HF. A total of 7 groups (237 in Taijiquan practice group and 237 in control group) were included in the study. The results of LF, HF and LF/HF heterogeneity test were I2 = 94. 5%, I2=82. 2% and I2=79. 6% respectively, which showed that there was no heterogeneity among various studies. Therefore, the random experimental model was used for data meta-analysis. The results showed that the values of LF, HF and LF/HF increased significantly. It shows that Taijiquan practice can improve the frequency domain index level of the elderly. The possible mechanism is that exercise stimulates the cardiac sympathetic nerve, enhances its impulse frequency, and presents the phenomenon of superiority of cardiac sympathetic nerve. Conclusion: With the increase of age, the autonomic nerve function and activity of the elderly decrease. There is a problem in the balance between sympathetic and parasympathetic nerves; Cardiac sympathetic nerve and cardiac vagus nerve activity disorder. Taijiquan exercise significantly promoted the HRV linear time domain indexes (SDNN, RMSSD) of the elderly; It also had a significant effect on HRV frequency domain indexes (LF, HF and LF/HF) in elderly men. SDNN refers to the standard deviation of cardiac cycle interval, RMSSD refers to the square root of the mean square difference of continuous cardiac cycle interval, and the values of SDNN and RMSSD determine the length of cardiac systolic interval, that is, the length of diastolic period of cardiac cycle. LF/HF represents the balance state of cardiac sympathetic nerve cardiac vagal nerve. The closer LF/HF is to 1, the more stable the balance state of cardiac sympathetic nerve cardiac vagal nerve is. According to meta-analysis: (1) After Taijiquan practice, the HRV time domain indexes SDNN and RMSSD of the elderly increased significantly, which showed that the vagus nerve tension increased significantly, indicating that Taijiquan practice can effectively improve the heart rate of the elderly, effectively prolong the SDNN of the elderly and reduce the possibility of cardiac muscle ischemia. It can improve the heart rate variability of the elderly and improve the function and activity of autonomic nerve; (2) After Taijiquan practice, HRV frequency domain indexes LF and LF/HF decreased, HF and TP indexes increased, TP difference was significant, and HF difference was very significant, indicating that Taijiquan practice can improve human aerobic exercise ability. The heart function of people who practice Taijiquan for a longer time showed more vitality than the elderly who do not exercise. The tension of vagus nerve increased significantly, the stability of sympathetic nerve increased, the tension of sympathetic nerve and parasympathetic nerve and the balance of sympathetic parasympathetic nerve were enhanced; (3) Meanwhile, Long term Taijiquan exercise can significantly reduce the TP value of elderly men, TP is the total power of HRV, representing the sum of HF (sympathetic active high frequency component), LF (sympathetic active low frequency component) and VLF (very low frequency component), It is also a typical frequency domain index of HRV. Its mechanism is that after long-term Taijiquan physical exercise, the body's aerobic exercise ability is relatively improved, the tension of vagus nerve is significantly increased, and the stability of sympathetic nerve is increased. There are still the following deficiencies and limitations in this study: Due to the limitation of retrieval of literature, we only conducted literature retrieval in these literature libraries at home and abroad, and the retrieval language only include Chinese and English, thus the relevant studies in other languages are not included in this paper, most studies have not formulated a detailed Taijiquan practice monitoring scheme, which not rule out the interference of uncontrollable and unmeasurable factors on the experimental results, and it is difficult to conduct subgroup analysis of the experiment. There are limitations in comparability, this study needs better design scheme and larger data sample size. More stringent intervention time to further study and verify.